A geographic comparison of the resting site fidelity behaviour in an intertidal limpet: Correlation with biological and physical factors - Nuñez, Jesus Dario (2014)
Many organisms vary their behaviour in response to environmental change. In stressful habitats motile organisms often exhibit behavioural patterns that are consistent with stress-minimizing strategies. In the present study we analysed the proportions of individuals with strong site fidelity and distances travelled by “unfaithful” individuals from their home scar at different temporal and spatial scales in the intertidal gastropod Siphonaria lessoni. We also assessed the behavioural response of S. lessoni to biological pressures such as conspecific population density and food availability (assessed by measures of chlorophyll a). The experiments were carried out in the arid climate of Patagonia on the rocky intertidal of Las Grutas (LG), and in the humid climate of The Pampas on the rocky intertidal of Mar del Plata (MDP) Argentina. At each site, shells of five hundred animals were marked with epoxy paint. Movement was measured as distance to a reference point after periods of one, five and ten days. Our results showed a positive relationship between food availability, site fidelity and distance to home scar for almost all observation days, but no relationship between population density and behavioural variables. Limpets in LG were more “faithful” than in MDP. Unfaithful limpets had the same mean displacement for all days and seasons except for Spring day-1 where MDP was higher than in LG and in Autumn day-10 where MDP was smaller than LG. The present results thus show differential response behaviour in intertidal limpets probably driven by the environmental conditions in which they live.